Cygnus survey with the Giant Metrewave Radio Telescope at 325 and 610 MHz: the catalog - Benaglia, Paula (2020)
Observations at the radio continuum band below the GHz are key when investigating the nature and properties of non-thermal sources, since at those frequencies their radio radiation is strongest. Therefore, the low radio frequency range is the best to spot possible counterparts to very high-energy (VHE) sources: relativistic particles of the same population are prone to be involved in radio and high energy radiation processes. Some of those counterparts to VHE sources can be stellar sources. Aims: The Cygnus region on the northern sky is one of the richest in this type of sources which are potential counterparts to VHE sources. We surveyed the central ~15sq deg of the Cygnus constellation at the bands of 325 and 610MHz, with angular resolutions and sensitivities of 10'' and 6'', and 0.5 and 0.2 mJy/beam, respectively. Methods: The data were collected during 172 hours along 2013 - 2017, using the Giant Metrewave Radio Telescope (GMRT) with 32MHz bandwidth, and were calibrated using the SPAM routines. The source extraction was carried out with the PyBDSF tool, followed by verification through visual inspection of every putative catalog candidate source, in order to determine its reliability. Results: In this first paper we present the catalog of sources, consisting of 1048 sources at 325MHz and 2796 sources at 610MHz. By cross-matching the sources from both frequencies with the objects of the SIMBAD database, we found possible counterparts for 143 of them. Most of the sources from the 325-MHz catalog (993) were detected at the 610MHz band, and their spectral index alpha was computed adopting S(nu) ~ nu^alpha. The spectral indices distribution shows its maximum at alpha=-1, characteristic of non-thermal emitters and possibly pointing at an extragalactic population.